A Novel Multiple Screw Distraction Reducer System in the Treatment of Scoliosis with a Severe Rib Hump - Zhipeng Deng; Liang Wang; Limin Liu; Lei Wang; Xi Yang; Yueming Song (Orthopaedic Surgery, 2024)
Objectives The treatment of scoliosis with a severe rib hump remains a major challenge. Traditional vertebral rotation techniques are not satisfactory, and thoracoplasty has many pulmonary complications that limit its application. A novel surgical device, the multiple screw distraction reducer (MSDR) system, provides longitudinal distraction during the corrective operation while at the same time providing lateral translation and axial derotation, which may facilitate the correction of a rib hump. This study was performed to investigate the effectiveness of the MSDR system for adolescent idiopathic scoliosis (AIS) with a severe rib hump. Methods This was a case‐matched study of patients with retrospectively collected data from our hospital between January 2017 and December 2021. Sixty‐eight patients who underwent one‐stage posterior pedicle screw‐instrumented spinal fusion were matched by the Cobb angle of the main curve and rib hump. All patients underwent a minimum of 2 years of follow‐up. The patients were divided into two groups: the MSDR group (using the MSDR system, n = 34) and the DVR group (using direct vertebral derotation, n = 34). The patients were evaluated for the height of the rib hump, deformity correction, complications, and SRS‐30 scores. The unpaired Student's t‐test and Pearson's χ2‐test were used to compare the outcome measures between the two groups. Multiple linear regression analysis was used to examine the variables that affected the correction of a rib hump. Results The rib hump was 30.21 ± 6.21 mm versus 29.35 ± 6.52 mm (p = 0.583) preoperatively and 9.18 ± 4.06 mm versus 13.82 ± 5.54 mm (p < 0.001) at the last follow‐up in the MSDR and DVR groups, respectively. The correction rates were 70.83% and 53.56%, respectively (p < 0.001). Preoperatively, the main thoracic curve was 58.43° ± 7.97° and 57.84° ± 6.32° (p = 0.736) and was corrected to 10.92° ± 5.47° and 19.14° ± 5.32° (p < 0.001) at last follow‐up in the MSDR and DVR group, respectively. Thoracic kyphosis was restored from 18.24° ± 5.19° and 17.98° ± 5.28° (p = 0.836) in the MSDR and DVR group to 24.59° ± 4.41° and 19.32° ± 4.96° (p < 0.001), respectively. Correction of apical vertebra rotation and translation in the main thoracic curve were significantly better in the MSDR group than in the DVR group (p < 0.05). There was no significant difference in the Lenke type, implant density, estimated blood loss, or follow‐up duration between the two groups, whereas the operation time in the DVR group was significantly less than that in the MSDR group. There were only two minor pulmonary complications in the MSDR group. At the last follow‐up, the MSDR group scored higher in terms of appearance and satisfaction (p < 0.05). Conclusion The MSDR system, enabling better coronal alignment, thoracic kyphosis, and axial derotation, could be a safe and effective technique for severe rib hump correction in AIS.